Punica granatum Linn. prevention of oral candidiasis in patients undergoing anticancer treatment - Manuela Gouvêa Campêlo dos SANTOS; Danúbia Roberta de Medeiros NÓBREGA; Rachel Reinaldo ARNAUD; Ronaldo Campêlo dos SANTOS; Daliana Queiroga de Castro GOMES; Jozinete Vieira PEREIRA
Abstract Introduction Oral candidiasis is considered one of the complications of antineoplastic therapy of head and neck. Studies show that herbal medicine has proven to be a promising alternative for the treatment of candidiasis. Objective To evaluate the effectiveness of the gel Punica granatum Linn. in the prevention of oral candidiasis in patients undergoing radiotherapy with or without chemotherapy for squamous cell carcinoma of the head and neck, and adverse effects associated with its use. Material and method It was performed a clinical trial, double blind, in the period 2012-2013, with patients seen at a referral hospital for cancer treatment. The sample consisted of 17 patients who did not have signs nor symptoms of oral candidiasis. These patients were divided into two groups: experimental (n=11): composed of patients who used the gel Punica granatum Linn. 6.25% since the beginning of the anticancer treatment and completed a week after the end of the treatment regimen; control (n=6): for patients who used the gel Miconazol 2%, following the same guidelines of the previous group. Data were tabulated and analyzed using descriptive statistics, the chi-square test and calculation of continuing Yates correction (p<0.05). Result There was no oral candidiasis in 63.6% of patients in the experimental group and in none of the control group patients. Conclusion Most patients who used the experimental gel showed no clinical signs of fungal infection, and there was no association of adverse effects.